2017
DOI: 10.1002/2016wr019737
|View full text |Cite
|
Sign up to set email alerts
|

Tropical river suspended sediment and solute dynamics in storms during an extreme drought

Abstract: Droughts, which can strongly affect both hydrologic and biogeochemical systems, are projected to become more prevalent in the tropics in the future. We assessed the effects of an extreme drought during 2015 on stream water composition in the Luquillo Mountains of Puerto Rico. We demonstrated that drought base flow in the months leading up to the study was sourced from trade‐wind orographic rainfall, suggesting a resistance to the effects of an otherwise extreme drought. In two catchments (Mameyes and Icacos), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 77 publications
4
44
0
Order By: Relevance
“…The results highlight the predominant contribution of a few large events to the annual SS load in this catchment, as already reported by several authors worldwide [7,[13][14][15]19,47]. Within the 12-year period (2004/2005-2016/2017), 15 events (<1% of time) produced about 40% of total recorded SS, suggesting a moderate irregularity in SS transport in the study area.…”
Section: Dynamics In Suspended Sediment Load At Different Time Scalessupporting
confidence: 85%
“…The results highlight the predominant contribution of a few large events to the annual SS load in this catchment, as already reported by several authors worldwide [7,[13][14][15]19,47]. Within the 12-year period (2004/2005-2016/2017), 15 events (<1% of time) produced about 40% of total recorded SS, suggesting a moderate irregularity in SS transport in the study area.…”
Section: Dynamics In Suspended Sediment Load At Different Time Scalessupporting
confidence: 85%
“…The lack of differentiation between concentrations on the rising and falling limbs of the storms indicates reservoirs of sediment both proximal and distal to the stream channel. This conclusion contrasts with many reports (Smith and Dragovich, 2009;Aich et al, 2014;Rose et al, 2018) including from the Luquillo Mountains and RI (Gellis, 2013;Clark et al, 2017). In an assessment of sensor-collected turbidity data during rewetting events following a major drought in RI, Clark et al (2017) reported a clockwise C-Q response for turbidity (Figure 6).…”
Section: Discussionmentioning
confidence: 59%
“…For example, correlation of in situ electrical conductivity (EC) measurements with discharge enabled Singley et al () to identify hydrologic mechanisms governing hysteretic behavior across the hydrograph in the McMurdo Dry Valleys of Antarctica. Using in‐stream sensors (combined with stable isotopes) for hydrograph separation enabled Clark et al () to show that new water, transmitted laterally downslope in the near subsurface, dominated storm hydrographs in events following extreme drought in the Rio Icacos watershed of the Luquillo CZO.…”
Section: Special Section On Concentration‐discharge Relations In the mentioning
confidence: 99%